Inflation and Economic Growth Paradox: A Co-integration Analysis in Nepal - Joshi, Uttam Lal (International Research Journal of MMC, 2021)
The empirical study investigates the relationship between economic growth, inflation and broad money supply in Nepal. Data since 1965 to 2020 are taken from World Bank and Autoregressive Distributive Lag Model is used to find cointegration between the variables to show long run and short run dynamics. Augmented Dickey- Fuller and Philips- Perron tests are conducted to find the unit roots in the model. Result shows the error correction term is negative (-0.75) and significant (0.0043) where bounds test supports the long run cointegration and error correction model suggest the speed of adjustment. The estimated regression equation is found robust and stable (serial correlation and heteroskedacity tests). The research shows inflation has short run and long run impact on economic growth so inflation should be kept within its threshold level from sound monetary and fiscal policy mechanism.